(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This article aimed to perform a systematic review of the literature regarding studies of Cognitive-Behavioral Therapies, about the deaf and hearing impaired community. For this, the search was made in the databases SciELO.org, PePSIC, LILACS, PsycINFO (APA), Scopus (Elsevier), PUBMED and Web of Science, through the CAPES Periodicals platform. The descriptors "deaf" and "hearing impaired" were combined with terms related to Cognitive-Behavioral Therapies. The languages defined were Portuguese, English and Spanish and the searches took place in April 2020. Additionally, the 10 studies analyzed were separated by categories, according to the sample surveyed (deaf and hearing impaired), and pointed to the possibility to assist deaf and hearing impaired people, adapting interventions to their singularities. Furthermore, the articles suggest new longitudinal research on the mental health of this population.